Malay Version of Acceptance and Action Questionnaire-II (AAQ-II): A Reliability and Validity Analysis in Non-Clinical Samples - Farhana Harzila Mohd Bahar; Mohd Amiruddin Mohd Kassim; Pang, Nicholas Tze Ping; Koh, Eugene Boon Yau; Assis Kamu; Ho, Chong Mun (Penerbit IIUM, 2022)
INTRODUCTION: Experiential avoidance is a key psychological process variable that measures the level of neglect or avoidance of unpleasant personal psychological experiences. It is highly correlated with the psychological flexibility construct, and both of these are important components in Acceptance and Commitment Therapy (ACT). Acceptance and Action Questionnaire-II (AAQ-II) has been used to measure both constructs and the Malay version of AAQ-II has been translated and validated in the clinical sample. Hence, this study aimed to assess the psychometric properties of the Malay version of AAQ-II in a non-clinical sample. MATERIALS AND METHOD: The participants were recruited from 3 campuses of Universiti Malaysia Sabah namely UMS-Labuan International Campus (UMSKAL), Sandakan campus, and the main campus in Kota Kinabalu. Convenience sampling was employed and the snowball method was used to recruit participants. All participants answered online questionnaires, which consist of sociodemographic information as well as the Malay version of AAQ-II, Mindfulness Awareness and Attention Scale (MAAS), General Health Questionnaire-12 (GHQ-12), and Balanced Index of Psychological Mindedness (BIPM). Both classical test theory and Rasch measurement theory were used to check the reliability and validity. RESULTS: There were 370 participants in this study. Malay version of AAQ-II demonstrated good psychometric properties with Cronbach’s alpha of 0.932, parallel reliability of 0.844, and satisfactory Rasch analysis. Exploratory factor analysis supported a one-factor model with 7-items. AAQ-II scores were positively correlated with depressive and anxiety scores, and lower levels of mindfulness and psychological mindedness, supporting the concurrent and convergent validity. CONCLUSION: Malay version of the AAQ-II has adequate reliability and validity in assessing psychological inflexibility in the non-clinical sample and hence could be a useful psychological instrument in assessing COVID-19 mental health effect.